Financial Sector Assessment Program Update - Albania : Insurance Core Principles - World Bank (World Bank, Washington, DC, 2014)
This assessment of Albania's compliance with the International Association of Insurance Supervisors (IAIS) Insurance Core Principles (ICP) was carried out as part of the 2013 Financial Sector Assessment Program (FSAP). Although this is the second FSAP for Albania, this is the first external assessment of Albania's compliance with the ICPs. The Albanian Financial Supervisory Authority (AFSA) has all the responsibility for insurance regulation and supervision in Albania. This assessment is based upon information made available to the assessor in preparation for and during the November 2013 FSAP mission. The AFSA contributed its self-assessment and a detailed update thereof at the individual criterion level. Further sectoral information (including responses to a questionnaire sent out in advance) was provided before and during the mission. Comprehensive documentation, including all relevant laws, by-laws and regulations were: (i) available on the AFSA's web-site; or (ii) provided to the assessor by the AFSA's management.